The role of the RhoA/Rho kinase pathway in angiogenesis and its potential value in prostate cancer (Review) - CHEN, WEIHUA (D.A. Spandidos, 2014)
Prostate cancer (PCa) remains a major cause of mortality among males in western countries, with little change in mortality rates observed over the past 25 years. Despite recent advances in therapy, treatment options for metastatic castration-resistant disease remain limited. In terms of chemotherapy, only the combination of docetaxel and prednisone has been shown to improve survival in these patients, but duration of response to therapy is short. There is a continuing unmet need for new systemic interventions that act either alone or synergistically with chemotherapy in patients with progressive PCa. Angiogenesis plays a critical role in tumor growth and metastasis in PCa. Several strategies have been used to target angiogenesis; however, it is becoming increasingly apparent that current anti-angiogenic therapies frequently achieve only modest effects in clinical settings. The RhoA/Rho kinase (ROCK) pathway plays a crucial role in the process of angiogenesis in PCa, and studies have demonstrated that ROCK inhibitors decrease VEGF-induced angiogenesis and tumor cell growth. However, further research is required to fully elucidate the molecular mechanisms involved in this pathway, and the potential value of modulating these mechanisms in the treatment of PCa. This study reviews the current understanding of the role of the RhoA/ROCK pathway in the process of angiogenesis in PCa, and the potential of this pathway as a therapeutic target in the future.